2019
DOI: 10.1101/638452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxytocin, Compulsion and Epilepsy: Insights from a Complex Behavioral and Neuronal Networks Association

Abstract: 18 19 Previously we have demonstrated that microinjection of oxytocin (OT) into the central nucleus of 20 amygdala (CeA) induces hypergrooming in Wistar rats, a model of compulsion. The Wistar 21 Audiogenic Rat (WAR) strain is a genetic model of generalized tonic-clonic seizures. Here we 22 quantified grooming behavior in WAR, with grooming scores, flowcharts and directed graphs of 23 syntactic and non-syntactic grooming chains, after bilateral administration of OT or saline (SAL) into 24 the CeA and investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
3
2
0
Order By: Relevance
“…WARs have also demonstrated high expression of both heteronuclear and messenger RNA of Oxt in paraventricular nucleus. In line with our results, Marroni et al 41 showed that WARs had more OXT/Fos double‐labeling in paraventricular nucleus than Wistar rats in control conditions. Altogether, these findings indicate that the WAR strain has endogenous alterations in the oxytocinergic system, and the increase in oxytocin plasma levels observed may occur due to an association between high paraventricular nucleus Oxt gene expression and increased oxytocinergic neuronal activity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…WARs have also demonstrated high expression of both heteronuclear and messenger RNA of Oxt in paraventricular nucleus. In line with our results, Marroni et al 41 showed that WARs had more OXT/Fos double‐labeling in paraventricular nucleus than Wistar rats in control conditions. Altogether, these findings indicate that the WAR strain has endogenous alterations in the oxytocinergic system, and the increase in oxytocin plasma levels observed may occur due to an association between high paraventricular nucleus Oxt gene expression and increased oxytocinergic neuronal activity.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, WARs also presented increased activity of oxytocin neurons 41 and Oxt expression in paraventricular nucleus, as demonstrated here. Therefore, this indicates that the paraventricular nucleus oxytocinergic neurons could be an integral part of the LiR in the WAR strain, being involved in their exploratory, anxiety‐related, social and compulsive behavioral changes 41,48,49 . However, in other models of limbic seizures, such as entorhinal cortex or amygdala electrical kindling, no changes in Oxt gene expression were found in supraoptic nuclei or paraventricular nucleus, probably due to the differences in neuroplasticity among models 10,27 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Behavioral changes that emerge after the postpartum period are mediated by a wide variety of neurotransmitters such as dopamine and neurohormones such as oxytocin (OT) and ACTH. WARs show higher ACTH secretion [28] and previous studies from our laboratory have suggested that WARs, could present alterations in the OT system [50], which might be related to a naturally excessive grooming when exposed to a novel environment. As a consequence, it would be interesting to study neurohormonal brain circuits in WARs and verify how they contribute to specific behaviors directed to the pup care, like LG and retrieving.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral changes that emerge after the postpartum period are mediated by a wide variety of neurotransmitters such as dopamine and neurohormones such as oxytocin (OT) and ACTH. WARs show higher ACTH secretion [28] and previous studies from our laboratory have suggested that WARs, could present alterations in the OT system [50], which might be related to a naturally excessive grooming when exposed to a novel environment. As a consequence, it would be interesting to study neurohormonal brain circuits in WARs and verify how they contribute to specific behaviors directed to the pup care, like LG and retrieving.…”
Section: Discussionmentioning
confidence: 99%